Negative electrode material, preparation method thereof and battery

By pre-filling lithium and silicon materials in the carbon material matrix of lithium-ion batteries and forming a carbon coating layer on the surface, the problem of low initial efficiency of silicon-based negative electrode materials is solved, the initial coulombic efficiency and energy density of the battery are improved, and the electrochemical performance is improved.

CN120709312APending Publication Date: 2025-09-26JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510714260.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-29
Publication Date
2025-09-26

AI Technical Summary

Technical Problem

The silicon-based negative electrode materials in existing lithium-ion batteries cause initial active lithium loss and irreversible capacity loss due to the formation of SEI film during the first charge and discharge process, affecting the battery's first discharge capacity/charge capacity ratio and energy density.

Method used

Lithium materials and/or lithium-containing compounds, as well as silicon materials and/or silicon-containing compounds, are pre-filled in the porous structure of the carbon material matrix, and a carbon coating layer is formed on the surface of the material to preferentially participate in the formation of the SEI film and avoid consuming lithium released from the positive electrode.

Benefits of technology

It significantly improves the first discharge capacity/charge capacity ratio, improves the volume expansion problem, enhances the electrochemical performance and fast charging performance of the battery, and reduces the interface impedance and material expansion risk.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a negative electrode material, a preparation method thereof and a battery. The negative electrode material provided by the invention comprises an inner core and a carbon coating layer coating at least part of the surface of the inner core, the inner core comprises a carbon material matrix and a modified material, and the modified material comprises lithium and / or a lithium-containing compound and silicon and / or a silicon-containing compound; the carbon material matrix has a porous structure, and the modified material is attached to the porous structure. The preparation method of the negative electrode material comprises the following steps: mixing a carbon material matrix precursor with a lithium source, and calcining to obtain a lithium-supplemented carbon material matrix precursor; then introducing a silicon source, and carrying out cracking deposition to obtain a lithium-silicon-supplemented carbon material; and taking the lithium-silicon-supplemented carbon material as an inner core, introducing a first carbon source into the lithium-silicon-supplemented carbon material, and carrying out second calcination to obtain the negative electrode material. The negative electrode material can make up for the initial active lithium loss and irreversible capacity loss of the material, so that the first efficiency is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of batteries, and specifically, to a negative electrode material, a preparation method thereof, and a battery. Background Art

[0002] Lithium-ion batteries (LIBs) are widely used in fields such as 3C electronic products, two / four-wheel electric vehicles, and industrial and commercial energy storage due to their long cycle life and high energy density. At the same time, due to the rapid development of electric vehicles, higher requirements are put forward for the energy density of lithium-ion batteries. LIBs mainly consist of four parts: a positive electrode, a separator, a negative electrode, and electrode foils. As a negative electrode, silicon-carbon materials can provide a theoretical specific capacity of about 3500 mAh / g, which is much higher than that of commercial graphite negative electrodes. It is a preferred negative electrode material for high-energy density batteries and one of the ideal materials for the negative electrode materials of next-generation lithium-ion batteries.

[0003] During the first charge and discharge process of lithium-ion batteries, the formation of the solid electrolyte interface (SEI) film of the silicon-based negative electrode battery doped with silicon-carbon will cause irreversible decomposition of the electrolyte, loss of initial active lithium (Li), and irreversible capacity loss, resulting in a decrease in the ratio of the first discharge capacity to the charge capacity (first efficiency), which will affect the capacity and energy density of the battery system, especially significantly for the silicon-based negative electrode battery system. Summary of the Invention

[0004] In view of this, the present invention is committed to providing a negative electrode material, a preparation method thereof, and a battery to solve the problem of low first efficiency of silicon-based negative electrode materials in the prior art.

[0005] To solve the above technical problems, the present application is implemented as follows: [[ID=…]]

[0006] The present invention provides a negative electrode material, which includes a core and a carbon coating layer covering at least part of the surface of the core;

[0007] The core includes a carbon material matrix and a modification material, and the modification material includes lithium and / or lithium-containing compounds, as well as silicon and / or silicon-containing compounds;

[0008] The carbon material matrix has a porous structure, and the modification material is attached to the porous structure.

[0009] In any embodiment, the modification material includes lithium, silicon, lithium-silicon alloy, and lithium silicate, and the lithium, silicon, lithium-silicon alloy, and lithium silicate are attached to the porous structure.

[0010] In any embodiment, the lithium-silicon alloy includes Li[[ID=…]] m Si n , where 0 < m ≤ 22, 0 < n ≤ 7, and 0 < m / n ≤ 4.4.

[0011] In any embodiment, the lithium silicate includes Li x Si y O z , where 0 ≤ x ≤ 22, 0 < y ≤ 7, 0 ≤ z ≤ 4, and 0 < x / y ≤ 4.4.

[0012] In any embodiment, in the XRD diffraction pattern of the negative electrode material, the differential absolute index F1 of the peak intensity at the position of 25° - 30° is F1 = |In(Ii / 2θi)|, and 1.8 ≤ F1 ≤ 6.5; where 2θi = Ix - Iy, Ix and Iy are values taken within 25° - 30°, the value of 2θi is within the range of 0.02 - 5, and Ii is the difference in the diffraction peak intensities corresponding to Ix and Iy.

[0013] In any embodiment, in the XRD diffraction pattern of the negative electrode material, the differential absolute index F2 of the peak intensity at the position of 45° - 55° is F2 = |In(Ie / 2θe)|, and 1.2 ≤ F2 ≤ 5.3; where 2θe = Iz - Ir, Iz and Ir are values taken within 45° - 55°, the value of 2θe is within the range of 0.02 - 5, and Ie is the difference in the diffraction peak intensities corresponding to Iz and Ir.

[0014] In any embodiment, based on the mass of the negative electrode material, the mass content of the carbon material matrix is 35% - 65%.

[0015] In any embodiment, the modification material includes lithium, silicon, lithium - silicon alloy, and lithium silicate. Based on the mass of the negative electrode material, the mass content of the lithium element is 0.2% - 60%.

[0016] In any embodiment, the modification material includes lithium, silicon, lithium - silicon alloy, and lithium silicate. Based on the mass of the negative electrode material, the mass content of the silicon element is 0.2% - 60%.

[0017] In any embodiment, the mass content of the lithium element ≤ the mass content of the silicon element.

[0018] In any embodiment, the modification material includes lithium, silicon, lithium - silicon alloy, and lithium silicate. Based on the mass of the negative electrode material, the mass content of the lithium - silicon alloy ≤ 10%.

[0019] In any embodiment, the modification material includes lithium, silicon, lithium - silicon alloy, and lithium silicate. Based on the mass of the negative electrode material, the mass content of the lithium silicate ≤ 10%.

[0020] In any embodiment, the thickness of the carbon coating layer is 0.8 nm - 80 nm.

[0021] In any embodiment, the particle size D of the negative electrode material v 50 is 2μm~35μm.

[0022] In any embodiment, the tap density of the negative electrode material is 0.6 to 1.4 m 3 / g.

[0023] The second aspect of the present application provides a method for preparing a negative electrode material, comprising the following steps:

[0024] S100, mixing a carbon material matrix precursor and a lithium source, and performing a first calcination to obtain a lithium-supplemented carbon material matrix precursor;

[0025] S200, introducing a silicon source into a lithium-supplemented carbon material matrix precursor to perform cracking and deposition to obtain a lithium-supplemented silicon-carbon material;

[0026] S300: Using the lithium-supplemented silicon-carbon material as a core, introducing a first carbon source into the lithium-supplemented silicon-carbon material, and performing a second calcination to form a carbon coating layer on at least part of the surface of the core, wherein the core includes a carbon material matrix with a porous structure and a modifying material attached to the porous structure, to obtain a negative electrode material.

[0027] In any embodiment, in step S100, the mass ratio of the carbon material matrix precursor to the lithium source is 100:(0.2-12).

[0028] In any embodiment, in step S100, the pore volume of the carbon material matrix precursor is 0.65 mL / g to 1.2 mL / g.

[0029] In any embodiment, based on the total pore volume of the carbon material matrix precursor, the volume of pores with diameters of 0.5 nm to 3 nm in the carbon material matrix precursor is ≥90%.

[0030] In any embodiment, the method for preparing the carbon material matrix precursor comprises the following steps:

[0031] After the second carbon source and the auxiliary agent are mixed, a pore-forming agent is introduced, and carbonization, cooling and pyrolysis are performed to obtain a carbon material matrix precursor.

[0032] In any embodiment, the lithium source includes at least one of metallic lithium, phenyllithium, butyllithium, lithium silicon alloy powder, lithium hydroxide, lithium peroxide, lithium oxide, lithium nitride, lithium sulfide and lithium fluoride;

[0033] In any embodiment, in step S100, the temperature of the first calcination is 300°C to 1300°C, the time of the first calcination is 30 minutes to 5 hours, and the atmosphere of the first calcination is an inert gas.

[0034] In any embodiment, the usage ratio of the second carbon source, the auxiliary agent and the pore-forming agent is 100 g: (0.1-5) g: (200-2500) L.

[0035] In any embodiment, the second carbon source comprises at least one of carbon black, coconut shell, bamboo, oak, phenolic resin, epoxy resin, furfural resin, urea-formaldehyde resin, needle coke, pitch coke, petroleum coke and mesocarbon microbeads.

[0036] In any embodiment, the auxiliary agent includes at least one of methanol, ethanol, propanol and isopropanol.

[0037] In any embodiment, the pore former includes at least one of oxygen, hydrogen, carbon monoxide, carbon dioxide, water, and ammonia.

[0038] In any embodiment, the carbonization temperature is 900° C. to 1400° C., and the carbonization time is 3 h to 14 h.

[0039] In any embodiment, the final temperature of the cooling is 400°C to 900°C.

[0040] In any embodiment, the pyrolysis temperature is 400° C. to 900° C., the pyrolysis time is 2 h to 8 h, and the pyrolysis atmosphere is an inert gas.

[0041] In any embodiment, in step S200, the flow rate of the silicon source is 100 mL / h to 400 mL / h.

[0042] In any embodiment, in step S200, the temperature of the pyrolysis deposition is 400-760° C., the time of the pyrolysis deposition is 20 min-6 h, and the atmosphere of the pyrolysis deposition is an inert gas.

[0043] In any embodiment, in step S200, the deposition amount of the silicon source is 15 wt% to 80 wt% of the lithium-compensated silicon-carbon material.

[0044] In any embodiment, in step S200, the silicon source includes at least one of monosilane, disilane, trisilane, dimethylsilane, hexamethyldisilane, dichlorodihydrogen silicon, trichlorosilane, silicon tetrachloride, or silicon tetrafluoride.

[0045] In any embodiment, in step S300, the flow rate of the first carbon source is 20 mL / h to 300 mL / h.

[0046] In any embodiment, in step S300, the first carbon source includes at least one of butene, ethylene, butyne, acetylene and propyne.

[0047] In any embodiment, in step S300, the heating rate of the second calcination is 1°C / min to 8°C / min, the temperature of the second calcination is 400 to 700°C, and the time of the second calcination is 1 hour to 6 hours.

[0048] A third aspect of the present application provides a battery, comprising a negative electrode sheet, wherein the negative electrode sheet comprises the above-mentioned negative electrode material, or comprises a negative electrode material prepared by the above-mentioned method for preparing the negative electrode material.

[0049] Through the above technical solution, the beneficial technical effects of the present invention are:

[0050] In the present application, the negative electrode material provided is pre-filled with lithium material and / or lithium-containing compound, as well as silicon material and / or silicon-containing compound in the porous structure of the carbon material matrix, and then a carbon coating layer is formed on the surface of the material. Among them, the lithium or lithium-containing compound in the silicon-carbon material preferentially participates in the formation of the electrolyte interface film (SEI) rather than consuming the lithium released from the positive electrode. During discharge, the positive electrode lithium can be more fully embedded, thereby compensating for the initial active lithium loss and irreversible capacity loss of the material, and significantly improving the first discharge capacity / charge capacity ratio (first effect). At the same time, the porous carbon structure in the carbon material matrix can improve the volume expansion problem of the negative electrode material, further improve the first effect and fast charging performance of the battery, and the outer carbon coating layer can avoid the problem of exposed modified materials attached to the porous structure, avoid contact between the modified material and the electrode liquid, reduce the SEI growth rate, and thus accelerate the diffusion of lithium ions in the material, improve electronic conductivity, reduce interface impedance, and avoid direct contact between the modified material and air and water. It basically does not produce gas, and does not cause the negative electrode material to break during rolling, constructing a stable material hierarchical structure; enhance the surface conductivity of electrons, optimize the ohmic polarization of the material, improve the material capacity, and further improve the electrochemical performance of the battery. Therefore, the first effect of the negative electrode material of this application at 0~1.5V is 96%~115%.

[0051] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION

[0052] The present invention discloses a negative electrode material, a method for preparing the same, and a battery. Those skilled in the art can refer to the contents herein and appropriately improve the process parameters to achieve the desired results. It should be noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments. It is obvious that relevant personnel can modify or appropriately alter and combine the methods and applications described herein without departing from the content, spirit, and scope of the present invention to implement and apply the technology of the present invention.

[0053] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms can mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A can include a single element or multiple elements. Item B can include a single element or multiple elements. Item C can include a single element or multiple elements.

[0054] The endpoints of the ranges and any values ​​disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range or the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered to be specifically disclosed herein.

[0055] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution. Unless otherwise specified, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.

[0056] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.

[0057] Generally, a battery includes an electrode assembly and an electrolyte. The electrode assembly includes a separator, a positive electrode sheet and a negative electrode sheet. Silicon-carbon material has become one of the most promising negative electrode active materials due to its high theoretical specific capacity. However, silicon-carbon negative electrode material will form an electrolyte interface film (SEI), causing irreversible decomposition of the electrolyte, loss of initial active Li and irreversible capacity loss, resulting in a decrease in the first discharge capacity / charge capacity ratio (first effect), which will affect the capacity and energy density of the battery system, and the impact on silicon-based negative electrode battery system is particularly significant.

[0058] Therefore, it is necessary to fully consider the characteristics of silicon-carbon negative electrode materials, improve the problem of lithium loss caused by interface film growth when silicon-carbon is used as the negative electrode material, and prepare silicon-carbon negative electrode materials with high first efficiency.

[0059] In view of this, the present application provides a negative electrode material, and also provides a negative electrode sheet and a battery containing the negative electrode material. The present application is described in detail below.

[0060] [Anode material]

[0061] In some embodiments, the present application provides a negative electrode material, comprising a core and a carbon coating layer coated on at least a portion of the surface of the core;

[0062] The core comprises a carbon material matrix and a modified material, and the modified material comprises lithium and / or a lithium-containing compound, and silicon and / or a silicon-containing compound;

[0063] The carbon material matrix has a porous structure, and the modified material is attached to the porous structure.

[0064] It should be noted that, in this application, the term "coating" is not limited to direct coating but also includes indirect coating. For example, when a coating layer coats an inner core, there may be no other structure between the coating layer and the outer surface of the inner core, or there may be one or more layers of other structures between the coating layer and the outer surface of the inner core. Preferably, there is no other structure between the coating layer and the outer surface of the inner core.

[0065] The coating layer is formed or coated on at least a portion of the surface of the core, which can protect or improve the core, thereby increasing the structural stability and reversible capacity of the core and optimizing the conductivity of the negative electrode material. The coating layer is formed or coated on at least a portion of the surface of the core, meaning that the coating layer can completely encapsulate the core within the coating layer, or it can only coat a portion of the outer surface of the core; that is, the coating layer can completely coat the core or only a portion of the surface of the core, preferably completely coating the core.

[0066] The negative electrode material of the present application is a core-shell structure, in which the core includes a carbon material matrix and a modified material, and the modified material includes lithium, silicon or a lithium-containing compound, a silicon-containing compound. The modified material is attached to the porous structure of the carbon material matrix and forms a carbon coating layer on the surface of the carbon material containing silicon and lithium, which alleviates the formation of the solid electrolyte membrane of the silicon-carbon negative electrode battery, compensates for the initial active Li loss and irreversible capacity loss of the material, improves the first coulombic efficiency, and thereby improves the system capacity and energy density of the battery.

[0067] The negative electrode material of the present application is suitable for use in lithium-ion batteries to alleviate the problem of low initial efficiency of existing silicon-carbon negative electrode materials for lithium-ion batteries.

[0068] The present application pre-fills lithium material and lithium-containing compound, as well as silicon material and silicon-containing compound in the porous structure of the carbon material matrix, and then forms a carbon coating layer on the surface of the material. For example, in some preferred embodiments, lithium material is pre-filled in the silicon-carbon material to obtain lithium-containing silicon-carbon material, and then a carbon coating layer is formed on the surface of the lithium-containing silicon-carbon material; illustratively, a porous carbon precursor containing lithium (i.e., a lithium-supplemented porous carbon precursor) is obtained by pre-filling lithium or pre-filling lithium compound on the porous carbon precursor of the silicon-carbon negative electrode material, and then silicon is deposited to obtain an inner core, and then a carbon coating layer can be formed on the surface of the inner core. Among them, the lithium or lithium-containing compound in the silicon-carbon material preferentially participates in the formation of SEI, rather than consuming the lithium released from the positive electrode. During discharge, the positive electrode lithium can be more fully embedded back, thereby compensating for the initial active Li loss and irreversible capacity loss of the material, and significantly improving the first discharge capacity / charge capacity ratio (first effect).

[0069] Compared with the method of first depositing silicon and then replenishing lithium, the present application obtains a lithium-containing porous carbon precursor (i.e., a lithium-replenishing porous carbon precursor) by pre-filling lithium or pre-filling lithium compounds on the porous carbon precursor of the silicon-carbon negative electrode material, and then depositing silicon. This can avoid excessive growth of crystalline Si caused by high temperature during lithium replenishment (the crystalline silicon increases and the structural stability of the material is poor), and obtain a high-first-efficiency silicon-carbon negative electrode material, which makes up for the consumption of irreversible lithium in the silicon-carbon material due to the formation of SEI film and the electrolyte. The ratio of the first lithium removal gram capacity at 0-1.5V to the first lithium insertion gram capacity at 0-1.5V (first coulomb efficiency) can reach more than 100%, which is much higher than the current first coulomb efficiency of conventional porous carbon deposited silicon of 80% to 90%, which is beneficial to improving the specific capacity of the material and the energy density of the battery.

[0070] At the same time, the porous carbon structure in the carbon material matrix can improve the volume expansion problem of the negative electrode material, further improve the first effect and fast charging performance of the battery, and the outer carbon coating layer can avoid the problem of exposed modified materials attached to the porous structure, avoid contact between the modified materials and the electrode liquid, reduce the SEI growth rate, and thus accelerate the diffusion of lithium ions, improve the electronic conductivity of the material, reduce the interface impedance, and avoid direct contact between the modified material and air and water, without gas production, and will not cause the negative electrode material to break during rolling, thereby constructing a stable material hierarchical structure; enhance the surface electronic conductivity, optimize the ohmic polarization of the material, improve the material capacity, and further improve the electrochemical performance of the battery.

[0071] In this application, the term "carbon coating" generally refers to a carbon-based material coated on the surface of a material through a specific process. In this application, the carbon coating can be formed by calcining a carbon source such as butene at high temperature to uniformly deposit the carbon coating on the surface of the core material.

[0072] In the present application, the term "carbon material matrix" generally refers to a material that is mainly composed of carbon elements and has no constant structure and properties.

[0073] In the present application, the modified material includes lithium and / or lithium-containing compounds, and silicon and / or silicon-containing compounds, which means that the modified material includes lithium materials and silicon materials. The lithium materials can be at least one of elemental lithium or lithium-containing compounds, and the silicon materials can be at least one of elemental silicon and silicon-containing compounds. Further, the above-mentioned lithium-containing compounds can be compounds containing lithium and silicon; the above-mentioned silicon-containing compounds can be compounds containing silicon and lithium. Preferably, the above-mentioned modified material contains elemental lithium, elemental silicon, and compounds containing lithium and silicon.

[0074] In some embodiments, the modified material includes lithium, silicon, lithium-silicon alloy, and lithium silicate, and the lithium, silicon, lithium-silicon alloy, and lithium silicate are attached to the porous structure.

[0075] In the present application, the modified material can be obtained by subjecting a lithium source such as metallic lithium, phenyllithium, or butyllithium to high-temperature treatment and then introducing a silicon source such as silane, disilane, or trisilane for high-temperature treatment. Among them, the lithium source and the silicon source will form lithium, silicon, lithium-silicon alloy, and lithium silicate. The above-mentioned lithium, silicon, lithium-silicon alloy, and lithium silicate act synergistically to improve the capacity of the anode material, improve the initial efficiency of the anode material, and reduce the expansion risk of the anode material. If all the lithium source and the silicon source are converted into silicon-lithium alloy and lithium silicate, it will exacerbate the expansion of the material, thereby affecting the cycle performance of the anode material.

[0076] In some embodiments, the lithium-silicon alloy includes Li m Si n , where 0 < m ≤ 22, 0 < n ≤ 7, and 0 < m / n ≤ 4.4. In the present application, by controlling the amounts of the lithium source and the silicon source, m can be in the range of 0 to 22 (excluding 0), n can be in the range of 0 to 7 (excluding 0), and m / n can be in the range of 0 to 4.4 (excluding 0).

[0077] In some embodiments, the lithium silicate includes Li x Si y O z , where 0 ≤ x ≤ 22, 0 < y ≤ 7, 0 ≤ z ≤ 4, and 0 < x / y ≤ 4.4. In the present application, by controlling the amounts of the lithium source and the silicon source, x can be in the range of 0 to 22, y can be in the range of 0 to 7 (excluding 0), and x / y can be in the range of 0 to 4.4 (excluding 0).

[0078] Optionally, in the above-mentioned anode material, the carbon material matrix can be porous carbon. Further, the porous carbon can be amorphous carbon.

[0079] Optionally, in the above-mentioned modified material, the particle size of the silicon crystal particles ≤ 4 nm, and the particle size of the lithium-silicon alloy crystal particles ≤ 8 nm; preferably, the particle size of the lithium-silicon alloy crystal particles ≤ 4 nm.

[0080] In the present invention, by regulating the particle size of the silicon crystal particles within the above range, high initial efficiency can be achieved while maintaining a low expansion rate.

[0081] Optionally, the silicon (Si) may be one or both of crystalline Si and amorphous Si.

[0082] In this application, in the XRD diffraction pattern of the negative electrode material, the peak intensity differential absolute index at 25 to 30 degrees satisfies the following characteristics (the peak at 25 to 30 degrees is the "111" crystal plane peak):

[0083] In some embodiments, in the XRD diffraction pattern of the negative electrode material, the peak intensity differential absolute index F1 at the position of 25° to 30° is F1 = |In(Ii / 2θi)|, and 1.8≤F1≤6.5; wherein Ix and Iy are values ​​taken within 25° to 30°, that is, the values ​​of Ix and Iy are taken within 25° to 30°, 2θi = Ix - Iy, the 2θi value is in the range of 0.02 to 5, and Ii is the difference in the diffraction peak intensity corresponding to Ix and Iy. "||" is the absolute value symbol, and "In()" is the exponential function. As an example, F1 can be any point value among 1.8, 2, 3, 4, 5, 6, and 6.5, or a range between any two of them. The peak intensity differential absolute index F1 at the position of 25° to 30° is within the above range, indicating that the peak at 25° to 30° is a "111" crystal plane peak.

[0084] In this application, in the XRD diffraction pattern of the negative electrode material, the peak intensity differential absolute index at 45 to 55 degrees satisfies the following characteristics (the peak at 45 to 55 degrees is the "220" crystal plane peak):

[0085] In some embodiments, in the XRD diffraction pattern of the negative electrode material, the peak intensity differential absolute index F2 at a position between 45° and 55° is F2 = |In(Ie / 2θe)|, and 1.2 ≤ F2 ≤ 5.3; wherein Iz and Ir are values ​​taken within the range of 45° to 55°, that is, the values ​​of Iz and Ir are taken within the range of 45° to 55°, 2θe = Iz - Ir, the 2θe value is in the range of 0.02 to 5, and Ie is the difference in the corresponding diffraction peak intensities of Iz and Ir. "||" is the absolute value symbol, and "In()" is the exponential function. For example, F2 can be any one of 1.2, 2, 3, 4, 5, and 5.3, or a range between any two of them. The peak intensity differential absolute index F2 at a position between 45° and 55° is within the above range, indicating that the peak between 45° and 55° is a "220" crystal plane peak.

[0086] In the present application, the test conditions of the XRD diffraction pattern of the above-mentioned negative electrode material are: the scanning angular velocity is 0.2 to 8 degrees / min, and the test angle range is 0 to 90 degrees.

[0087] In this application, by controlling F1 and F2 within the above range, it is possible to ensure that Li m Si n 、Li x Si y O z The content of F1 and F2 is within the appropriate range, which is beneficial to improving the initial efficiency of the negative electrode material. If F1 and F2 are too large, it indicates that the negative electrode material contains Li m Si n 、Li x Si y O z Excessive content of F1 and F2 will lead to the formation of crystalline silicon, reducing the initial efficiency of the negative electrode material. It will also aggravate the expansion of the negative electrode material, causing the material to break and increase the cost. If F1 and F2 are too small, it will not be possible to improve the low initial efficiency of the silicon-carbon negative electrode material and achieve the expected technical effect.

[0088] In some embodiments, the mass content of the carbon material matrix is ​​35% to 65% based on the mass of the negative electrode material. As an example, the mass content of the carbon material matrix can be any one of 35%, 40%, 45%, 50%, 55%, 60%, and 65%, or a range between any two of the mass content of the negative electrode material.

[0089] In some embodiments, the modified material includes lithium, silicon, a lithium-silicon alloy, and lithium silicate, and the mass content of the lithium element is 0.2% to 60% based on the mass of the negative electrode material. As an example, the mass content of the lithium element can be any one of 0.2%, 0.5%, 1%, 5%, 10%, 20%, 30%, 40%, 50%, and 60%, or a range therebetween, based on the mass of the negative electrode material.

[0090] In some embodiments, the modified material includes lithium, silicon, a lithium-silicon alloy, and lithium silicate, and the mass content of silicon is 0.2% to 60% based on the mass of the negative electrode material. As an example, the mass content of silicon can be any one of 0.2%, 0.5%, 1%, 5%, 10%, 20%, 30%, 40%, 50%, and 60%, or a range therebetween, based on the mass of the negative electrode material.

[0091] In some embodiments, the mass content of lithium element is less than or equal to the mass content of silicon element.

[0092] Optionally, in the above negative electrode material, 0.2 wt% ≤ the mass content of lithium element ≤ the mass content of silicon element ≤ 60 wt%; preferably, 2 wt% ≤ the mass content of lithium element ≤ the mass content of silicon element ≤ 55 wt%.

[0093] In some embodiments, the modified material includes lithium, silicon, a lithium-silicon alloy, and lithium silicate, and the mass content of the lithium-silicon alloy is ≤10% based on the mass of the negative electrode material. As an example, the mass content of the lithium-silicon alloy can be any one of 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, and 10%, or a range therebetween, based on the mass of the negative electrode material.

[0094] In some embodiments, the modified material includes lithium, silicon, a lithium-silicon alloy, and lithium silicate, and the mass content of the lithium silicate is ≤10% based on the mass of the negative electrode material. As an example, the mass content of the lithium silicate can be any one of 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, and 10%, or a range therebetween, based on the mass of the negative electrode material.

[0095] In the present application, by controlling the mass content of lithium, silicon, lithium silicon alloy and lithium silicate in the carbon material matrix and modified material within the above range, it is possible to effectively solve the problem of low initial efficiency of silicon-carbon negative electrode materials, improve the system capacity and energy density of the battery, and alleviate the expansion problem of the negative electrode material.

[0096] In some embodiments, the thickness of the carbon coating layer is 0.8 nm to 80 nm. As an example, the thickness of the carbon coating layer can be any value among 0.8 nm, 1 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm and 80 nm, or any range therebetween.

[0097] In the present application, by controlling the thickness of the carbon coating layer within the above range, the coating layer can form a continuous and dense protective layer, which can avoid the problem of exposed modified materials attached to the porous structure, avoid contact between the modified materials and the electrode liquid, reduce the SEI growth rate, and thus accelerate the diffusion of lithium ions in the material, improve electronic conductivity, reduce interface impedance, and avoid direct contact between the modified materials and air and water, without producing gas, and will not cause the negative electrode material to break during rolling, thereby constructing a stable material hierarchical structure; improving the surface conductivity, optimizing the material ohmic plan, improving the material capacity, and further improving the electrochemical performance of the battery. If the thickness of the coating layer is too thick, the diffusion path of lithium ions will be extended, the diffusion impedance will increase, and the rate performance and cycle stability of the negative electrode material will be affected. If the thickness of the coating layer is too thin, the effect of avoiding contact between the modified material and the electrolyte will not be achieved.

[0098] In some embodiments, the particle size D of the negative electrode material v 50 is 2 μm to 35 μm, preferably 2.5 μm to 35 μm. As an example, the particle size D of the negative electrode material v50 may be any one of 2 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm and 35 μm, or a range of values ​​between any two of them.

[0099] In some embodiments, the tap density of the negative electrode material is 0.6 to 1.4 m 3 As an example, the tap density of the negative electrode material can be 0.6 m 3 / g, 0.7m 3 / g, 0.8m 3 / g, 0.9m 3 / g、1m 3 / g, 1.1m 3 / g, 1.2m 3 / g, 1.3m 3 / g and 1.4m 3 Any point value in / g or any range of values ​​between them.

[0100] In an embodiment of the present application, the first delithiation capacity of the negative electrode material at 0-1.5V is 850-3200mAh / g, for example, 850mAh / g, 900mAh / g, 1000mAh / g, 1100mAh / g, 1200mAh / g, 1300mAh / g, 1400mAh / g, 1500mAh / g, 1600mAh / g, 1700mAh / g, 1800mAh / g, 1900mAh / g, 2000mAh / g, 2100mAh / g, 2200mAh / g, 2300mAh / g, 2500mAh / g, 2600mAh / g, 2700mAh / g, 2800mAh / g, 2900mAh / g, 3000mAh / g, 3100mAh / g, 3200mAh / g, or any value between these values.

[0101] In an embodiment of the present application, the first efficiency (the ratio of the first lithium removal capacity in the range of 0 to 1.5 V to the first lithium insertion capacity in the range of 0 to 1.5 V, the first coulombic efficiency) of the negative electrode material is between 90% and 128%, for example, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, 101%, 102%, 103%, 104%, 105%, 106%, 107%, 108%, 109%, 110%, 120%, 125%, 127%, 128%, or any value therebetween.

[0102] The provided negative electrode material comprises a core and a carbon coating covering at least a portion of the core's surface. The core comprises a carbon material matrix and a modified material, the modified material comprising lithium and / or a lithium-containing compound, and silicon and / or a silicon-containing compound. The carbon material matrix has a porous structure, and the modified material is attached to the porous structure. This negative electrode material compensates for the material's initial active lithium loss and irreversible capacity loss, thereby improving its initial coulombic efficiency.

[0103] [Method for preparing negative electrode material]

[0104] The second aspect of the present application provides a method for preparing a negative electrode material, comprising the following steps:

[0105] S100, mixing a carbon material matrix precursor and a lithium source, and performing a first calcination to obtain a lithium-supplemented carbon material matrix precursor;

[0106] S200, introducing a silicon source into a lithium-supplemented carbon material matrix precursor to perform cracking and deposition to obtain a lithium-supplemented silicon-carbon material;

[0107] S300, using the lithium-supplemented silicon-carbon material as the core, introducing a first carbon source into the lithium-supplemented silicon-carbon material, and performing a second calcination to form a carbon coating layer on at least part of the surface of the core, wherein the core includes a carbon material matrix with a porous structure and a modified material attached to the porous structure, thereby obtaining a negative electrode material.

[0108] In the present application, a method for preparing a negative electrode material is provided, wherein a carbon material matrix precursor and a lithium source are mixed and calcined to obtain a carbon material matrix precursor pre-filled with lithium. A silicon source is then introduced to deposit silicon in the carbon material matrix precursor pre-filled with lithium, and finally a carbon coating layer is applied to obtain the negative electrode material. That is, in the present application, lithium is first pre-filled in the carbon material matrix and then silicon is deposited. This can effectively avoid the excessive growth of crystalline silicon caused by the high temperature of lithium replenishment when silicon is first deposited and then lithium is replenished (the increase in crystalline silicon leads to poor structural stability of the material), and compensates for the irreversible lithium consumption of the silicon-carbon material due to the formation of the SEI film and the electrolyte. The ratio of the first lithium removal gram capacity at 0-1.5V to the first lithium insertion gram capacity at 0-1.5V (the first coulombic efficiency) can reach more than 100%, which is much higher than the first coulombic efficiency (80%-90%) of conventional porous carbon-deposited silicon, which is beneficial to improving the specific capacity of the material and the energy density of the battery.

[0109] It should be understood that all the features and advantages described above for the “negative electrode material” are also applicable to the “method for preparing the negative electrode material” and will not be described in detail here.

[0110] In some embodiments, in step S100, the mass ratio of the carbon material matrix precursor to the lithium source is 100:(0.2-12). As an example, the mass ratio of the carbon material matrix precursor to the lithium source can be any one of 100:0.2, 100:0.5, 100:0.8, 100:1, 100:2, 100:3, 100:4, 100:5, 100:6, 100:7, 100:8, 100:9, 100:10, 100:11, and 100:12, or a range between any two of them.

[0111] In the present application, by controlling the mass ratio of the carbon material matrix precursor and the lithium source within the above range, it is possible to ensure that there is sufficient lithium source to effectively cover the lithium consumption required for the formation of the SEI film, make up for the initial active lithium loss and irreversible capacity of the material, and improve the first coulombic efficiency of the negative electrode material. If the amount of lithium source is too much, unreacted free lithium may remain in the electrode and continue to react with the electrolyte, resulting in an excessively thick SEI film and increased interfacial impedance. If the amount of lithium source is too little, insufficient lithium replenishment will result, and the first cycle efficiency of the material cannot be effectively improved.

[0112] In some embodiments, in step S100, the pore volume of the carbon material matrix precursor is 0.65 mL / g to 1.2 mL / g. As an example, in step S100, the pore volume of the carbon material matrix precursor can be any one of 0.65 mL / g, 0.7 mL / g, 0.75 mL / g, 0.8 mL / g, 0.85 mL / g, 0.9 mL / g, 0.95 mL / g, 1 mL / g, 1.05 mL / g, 1.1 mL / g, 1.15 mL / g, and 1.2 mL / g, or a range of values ​​therebetween.

[0113] In some embodiments, based on the total pore volume of the carbon material matrix precursor, the volume of pores in the carbon material matrix precursor having a diameter of 0.5 nm to 3 nm is ≥ 90%. As an example, based on the total pore volume of the carbon material matrix precursor, the volume of pores in the carbon material matrix precursor having a diameter of 0.5 nm to 3 nm can be 90%, 92%, 95%, 96%, 98%, etc.

[0114] In the present application, by controlling the pore parameters of the carbon material matrix precursor within the above range, more embedding sites and dispersion channels can be provided for the lithium source and subsequent silicon source, providing conditions for the subsequent compensation of the initial active Li loss of the material.

[0115] In some embodiments, in step S100, the lithium source includes, but is not limited to, at least one of metallic lithium, phenyllithium, butyllithium, lithium silicon alloy powder, lithium hydroxide, lithium peroxide, lithium oxide, lithium nitride, lithium sulfide, and lithium fluoride.

[0116] In some embodiments, in step S100, the temperature of the first calcination is 300° C. to 1300° C., the time of the first calcination is 30 minutes to 5 hours, and the atmosphere of the first calcination is an inert gas. As an example, the temperature of the first calcination can be any value among 300° C., 400° C., 500° C., 600° C., 700° C., 800° C., 900° C., 1000° C., 1100° C., 1200° C., and 1300° C., or a range between any two of them, the time of the first calcination can be any value among 30 minutes, 1 hour, 2 hours, 3 hours, 4 hours, and 5 hours, or a range between any two of them, and the inert atmosphere can be nitrogen and / or argon.

[0117] During the first calcination process, the decomposition of the lithium source is driven by high temperature, which promotes the combination of lithium and carbon matrix, realizes the uniform immobilization of lithium in the carbon material matrix precursor and the pre-lithium functionalization, and lays the foundation for the subsequent improvement of the initial effect of the negative electrode material.

[0118] In some embodiments, in step S100, the method for preparing a carbon material matrix precursor includes the following steps:

[0119] After the second carbon source and the auxiliary agent are mixed, a pore-forming agent is introduced, and carbonization, cooling and pyrolysis are performed to obtain a carbon material matrix precursor.

[0120] In some embodiments, the usage ratio of the second carbon source, the auxiliary agent, and the pore-forming agent is 100 g: (0.1-5) g: (200-2500) L. As an example, the usage ratio of the second carbon source, the auxiliary agent, and the pore-forming agent can be any one of 100:0.1 g:200 L, 100:1 g:500 L, 100:2 g:1000 L, 100:3 g:1500 L, 100:5 g:2000 L, and 100:5 g:2500 L, or a range therebetween.

[0121] In some embodiments, the second carbon source includes, but is not limited to, at least one of carbon black, coconut shell, bamboo, oak, phenolic resin, epoxy resin, furfural resin, urea-formaldehyde resin, needle coke, pitch coke, petroleum coke, and mesocarbon microbeads.

[0122] In some embodiments, the auxiliary agent includes, but is not limited to, at least one of methanol, ethanol, propanol, and isopropanol.

[0123] In some embodiments, the pore former includes, but is not limited to, at least one of oxygen, hydrogen, carbon monoxide, carbon dioxide, water, and ammonia.

[0124] In some embodiments, the carbonization temperature is 900° C. to 1400° C., and the carbonization time is 3 hours to 14 hours. As an example, the carbonization temperature can be any one of 900° C., 1000° C., 1100° C., 1200° C., 1300° C., and 1400° C., or a range therebetween, and the carbonization time can be any one of 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, and 14 hours, or a range therebetween.

[0125] In some embodiments, the final temperature of the cooling is 400° C. to 900° C. As an example, the final temperature of the cooling can be any one of 400° C., 500° C., 600° C., 700° C., 800° C., and 900° C., or a range therebetween.

[0126] In some embodiments, the pyrolysis temperature is 400° C. to 900° C., the pyrolysis time is 2 h to 8 h, and the pyrolysis atmosphere is an inert gas. As an example, the heating temperature is any one of 400° C., 500° C., 600° C., 700° C., 800° C., and 900° C., or a range between any two thereof, and the pyrolysis time is any one of 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, and 8 h, or a range between any two thereof.

[0127] In this application, the preparation of the carbon material matrix precursor involves promoting the growth of graphite crystallites within the carbon source during high-temperature carbonization. The additive undergoes cracking, generating carbon deposits on the carbon source surface. The pore-forming agent then undergoes a gasification reaction with the carbon source, creating pores. Pyrolysis further enhances the stability of the resulting carbon structure. Through staged temperature control and reaction regulation, the carbon material achieves a high specific surface area, good conductivity, and structural stability.

[0128] As an example, in step S100, the method for preparing a carbon material matrix precursor includes the following steps:

[0129] Mix 100g of a second carbon source such as carbon black and 0.1-5g of an additive such as methanol, put them into a heating furnace and introduce 200-2500L of a pore-forming agent, carbonize them at 900-1400°C for 3-14h, cool them to 400-900°C after carbonization, and pyrolyze them at 400-900°C in an inert atmosphere for 2-8h. After the pyrolysis, wash and crush the resulting product to obtain a carbon material matrix precursor.

[0130] As an example, in step S100, the method for preparing the lithium-supplemented carbon material matrix precursor includes the following steps:

[0131] Mix 100g of a carbon material matrix precursor with a pore volume of 0.65-1.2mL / g (pore volume ≥90% with a pore diameter of 0.5nm-3nm) and 0.2-12g of a lithium source such as metallic lithium, phenyllithium, etc., and perform a first calcination at 300-1300°C in an inert atmosphere for 30min-5h. After the first calcination, the resulting product is naturally cooled to room temperature and then crushed to obtain a lithium-supplemented carbon material matrix precursor.

[0132] In some embodiments, in step S200, the flow rate of the silicon source is 100 mL / h to 400 mL / h. As an example, the flow rate of the silicon source can be any one of 100 mL / h, 150 mL / h, 180 mL / h, 200 mL / h, 260 mL / h, 300 mL / h, 350 mL / h, and 400 mL / h, or a range therebetween.

[0133] In some embodiments, in step S200, the temperature of the pyrolysis deposition is 400-760° C., the time of the pyrolysis deposition is 20 minutes to 6 hours, and the atmosphere of the pyrolysis deposition is an inert gas. As an example, the temperature of the pyrolysis deposition can be any value among 400° C., 450° C., 500° C., 550° C., 600° C., 650° C., 700° C., 750° C., and 760° C., or a range between any two values, the time of the pyrolysis deposition can be any value among 20 minutes, 30 minutes, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, and 6 hours, or a range between any two values, and the atmosphere can be nitrogen and / or argon.

[0134] During the cracking and deposition process, high temperature drives the decomposition of the silicon source, and it can also react with the lithium in the lithium-supplemented carbon material matrix precursor to generate silicon-lithium alloy and lithium silicate. The silicon-lithium alloy, lithium silicate, silicon and lithium work synergistically to improve the initial effect of the negative electrode material.

[0135] In some embodiments, in step S200, the deposition amount of the silicon source is 15 wt% to 80 wt% of the lithium-compensated silicon-carbon material. As an example, the deposition amount of the silicon source is any one of 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, 70 wt%, 75 wt%, and 80 wt% of the lithium-compensated silicon-carbon material, or a range between any two of these.

[0136] In some embodiments, in step S200 , the silicon source includes, but is not limited to, at least one of monosilane, disilane, trisilane, dimethylsilane, hexamethyldisilane, dichlorosilane, trichlorosilane, silicon tetrachloride, or silicon tetrafluoride.

[0137] As an example, the method for preparing the lithium-supplemented silicon-carbon material in step S200 includes the following steps:

[0138] In an inert atmosphere at 400-760° C., a silicon source such as monosilane is introduced into a lithium-replenished carbon material matrix precursor at a flow rate of 100 mL / h-400 mL / h to obtain a lithium-replenished silicon-carbon material with a silicon source deposition amount of 15-80 wt%.

[0139] In some embodiments, in step S300, the flow rate of the first carbon source is 20 mL / h to 300 mL / h. As an example, the flow rate of the first carbon source can be any one of 20 mL / h, 100 mL / h, 150 mL / h, 180 mL / h, 250 mL / h, 300 mL / h, 350 mL / h, and 400 mL / h, or a range therebetween.

[0140] In some embodiments, in step S300, the first carbon source includes, but is not limited to, at least one of butene, ethylene, butyne, acetylene, and propyne.

[0141] In some embodiments, in step S300, the heating rate of the second calcination is 1°C / min to 8°C / min, the temperature of the second calcination is 400°C to 700°C, and the time of the second calcination is 1 hour to 6 hours. As an example, the heating rate of the second calcination can be any one of 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, and 8°C / min, or a range between any two of them, the temperature of the second calcination can be any one of 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, and 700°C, or a range between any two of them, and the time of the second calcination can be any one of 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, and 6 hours, or a range between any two of them.

[0142] During the second calcination process, the first carbon source is pyrolyzed to form a carbon coating layer on the surface of the lithium-supplemented silicon-carbon material, avoiding the problem of exposed modified materials attached to the porous structure, preventing the modified materials from contacting the electrode liquid, reducing the SEI growth rate, and thereby accelerating the diffusion of lithium ions in the material, improving electronic conductivity, and reducing interface impedance.

[0143] As an example, in step S300, the method for preparing the negative electrode material includes the following steps:

[0144] A lithium-supplemented silicon-carbon material is used as the core, which is sent to a fluidized bed or a rotary kiln, and the temperature is raised to a second calcination temperature of 400-700°C at a rate of 1°C / min-8°C / min. A first carbon source such as butene is introduced at a flow rate of 20mL / h-300mL / h, and the material is kept at the second calcination temperature for 1-6 hours to form a carbon coating layer on at least part of the surface of the core. The core includes a carbon material matrix with a porous structure and a modified material attached to the porous structure to obtain a negative electrode material.

[0145] [Battery]

[0146] A third aspect of the present application provides a battery, which includes a negative electrode sheet, and the negative electrode sheet includes the above-mentioned negative electrode material, or includes the negative electrode material prepared by the above-mentioned method for preparing the negative electrode material.

[0147] In some embodiments, the battery further comprises a positive electrode sheet, an electrolyte, and a separator. That is, the battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator.

[0148] In the present application, the battery may be a lithium-ion battery. The battery stack type may be, for example, a wound or laminated battery, and the structural type may be, for example, a square shell (aluminum shell, steel shell, etc.), a soft pack battery, or a cylindrical battery, etc., without specific limitation. The battery has a high capacity, good cycle performance, and a long service life.

[0149] In the present application, there is no limitation on the specific materials and structures of the positive electrode sheet, separator, and electrolyte in the battery. Components and structures that are well known in the art and can be used for secondary batteries can be selected as long as the purpose of the present application can be achieved.

[0150] In some embodiments, the isolation membrane may be a combination of one or more materials including but not limited to polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester, and natural fibers.

[0151] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer disposed on at least one surface of the negative electrode current collector in the thickness direction; the negative electrode active layer includes a negative electrode active material, and the negative electrode active material includes the negative electrode material prepared above.

[0152] In some embodiments, the negative electrode active layer further includes a first conductive agent and a first binder.

[0153] In some embodiments, the first conductive agent includes at least one of conductive carbon black, silver powder, nickel powder, graphite whiskers, conductive Ketjen black, conductive acetylene black, conductive graphene, single-walled carbon nanotubes, multi-walled carbon nanotubes, and oligo-walled carbon nanotubes.

[0154] In some embodiments, the first binder includes at least one of sodium / lithium polyacrylate, polymethyl methacrylate, polyethyl acrylate, sodium / lithium polyacrylate-methyl / ethyl / propyl acrylate, sodium polyacrylate / lithium-acrylonitrile, sodium polyacrylate / lithium-butadiene-acrylonitrile, carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, and polyvinylidene fluoride.

[0155] In some embodiments, the negative electrode active material may further include graphite material.

[0156] In the present application, the graphite material can be obtained by shaping, calcining, granulating or coating carbon-containing substances, wherein the carbon-containing compounds include, but are not limited to, needle tar, coal tar, asphalt tar, and petroleum coke.

[0157] In some embodiments, the mass ratio of the negative electrode active material, the first conductive agent, and the first binder in the negative electrode active layer is (86-99):(0.2-6):(0.8-8). As an example, the mass ratio of the negative electrode active material, the conductive agent, and the binder in the negative electrode active layer can be any one of 86:0.2:0.8, 88:1:2, 90:2:4, 92:3:5, 95:4:6, 98:5:8, and 99:6:8, or a range between any two of them.

[0158] In some embodiments, the surface density of the negative electrode active layer is 0.003 to 0.025 g / cm 2 As an example, the surface density of the negative electrode active layer can be 0.003 g / cm 2 , 0.005g / cm 2 , 0.01g / cm 2 , 0.015g / cm 2 , 0.02g / cm 2 and 0.025g / cm 2 Any point value in or any range of values ​​between them.

[0159] In some embodiments, a method for preparing a negative electrode sheet comprises the following steps:

[0160] Mixing the negative electrode active material, a portion of the first conductive agent, a portion of the first binder, and a solvent to obtain a first negative electrode slurry;

[0161] mixing the first negative electrode slurry, the remaining first conductive agent, a portion of the first binder, and a solvent to obtain a second negative electrode slurry;

[0162] mixing the second negative electrode slurry, the remaining first binder and the solvent to obtain a third negative electrode slurry;

[0163] The third negative electrode slurry is coated on at least one surface of the negative electrode current collector along the thickness direction, and is dried and rolled to obtain a negative electrode sheet.

[0164] In some embodiments, the solid content of the second negative electrode slurry is 35 wt % to 50 wt %. As an example, the solid content of the second negative electrode slurry can be any one of 35 wt %, 40 wt %, 45 wt % and 50 wt %, or a range therebetween.

[0165] In some embodiments, the solid content of the third negative electrode slurry is 30 wt % to 48 wt %. As an example, the solid content of the third negative electrode slurry can be any one of 30 wt %, 32 wt %, 35 wt %, 40 wt %, 45 wt % and 48 wt %, or a range therebetween.

[0166] In some embodiments, the fineness of the third negative electrode slurry is ≤45 μm. As an example, the fineness of the third negative electrode slurry can be any one of 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm and 45 μm, or a range between any two thereof.

[0167] In some embodiments, the battery includes a positive electrode sheet, which includes a positive electrode collector and a positive electrode active layer disposed on at least one surface of the positive electrode collector in a thickness direction; the positive electrode active layer includes a positive electrode active material.

[0168] In some embodiments, the positive active material includes a lithium-containing compound and / or sulfur.

[0169] In some embodiments, the lithium-containing compound includes, but is not limited to, at least one of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese aluminum oxide, lithium-rich manganese-based, lithium iron phosphate, lithium manganese phosphate, lithium iron manganese phosphate, lithium manganese oxide, and lithium nickel manganese oxide.

[0170] In some embodiments, the positive electrode active layer further includes a second conductive agent, a second binder, and an electrolyte.

[0171] In some embodiments, the second conductive agent includes, but is not limited to, at least one of conductive carbon black, silver powder, nickel powder, graphite whiskers, conductive Ketjen black, conductive acetylene black, conductive graphene, single-walled carbon nanotubes, multi-walled carbon nanotubes, and oligo-walled carbon nanotubes.

[0172] In some embodiments, the second binder includes, but is not limited to, at least one of sodium / lithium polyacrylate, polymethyl methacrylate, polyethyl acrylate, sodium / lithium polyacrylate-methyl / ethyl / propyl acrylate, sodium polyacrylate / lithium-acrylonitrile, sodium polyacrylate / lithium-butadiene-acrylonitrile, carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, and polyvinylidene fluoride.

[0173] In some embodiments, the electrolyte includes, but is not limited to, at least one of lithium lanthanum zirconate, lithium lanthanum tantalate, lithium lanthanum zirconate tantalate, lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, lithium chlorophosphate, and lithium germanium sulfide.

[0174] In some embodiments, the mass ratio of the positive electrode active material, the second conductive agent, the second binder, and the electrolyte in the positive electrode active layer is (84-99): (0.2-6): (0.6-8): (0.2-2). As an example, the mass ratio of the positive electrode active material, the conductive agent, and the binder in the positive electrode active layer can be any one of 84:0.2:0.8:0.2, 86:0.2:0.8:0.2, 88:1:2:0.5, 90:2:4:1, 92:3:5:1.2, 95:4:6:1.5, 98:5:8:2, and 99:6:8:2, or a range between any two of them.

[0175] In some embodiments, the surface density of the positive electrode active layer is 0.01 to 0.085 g / cm 2 As an example, the surface density of the positive electrode active layer can be 0.01 g / cm 2 , 0.02g / cm 2 , 0.3g / cm 2 , 0.04g / cm 2 , 0.05g / cm 2 , 0.06g / cm 2 , 0.07g / cm 2 , 0.08g / cm 2 and 0.085g / cm 2 Any point value in or any range of values ​​between them.

[0176] In some embodiments, a method for preparing a positive electrode sheet comprises the following steps:

[0177] Mixing the positive electrode active material, part of the second conductive agent, part of the second binder and a solvent to obtain a first positive electrode slurry;

[0178] mixing the first positive electrode slurry, the remaining second conductive agent, a portion of the second binder, an electrolyte, and a solvent to obtain a second positive electrode slurry;

[0179] mixing the second positive electrode slurry, the remaining second binder and the solvent to obtain a third positive electrode slurry;

[0180] The third positive electrode slurry is coated on at least one side surface of the positive electrode current collector along the thickness direction, and is dried and roll-pressed to obtain a positive electrode sheet.

[0181] In some embodiments, the solid content of the second positive electrode slurry is 65 wt % to 85 wt %. As an example, the solid content of the second positive electrode slurry can be any one of 65 wt %, 70 wt %, 75 wt %, 80 wt % and 85 wt %, or a range therebetween.

[0182] In some embodiments, the solid content of the third positive electrode slurry is 60 wt % to 80 wt %. As an example, the solid content of the third positive electrode slurry can be any one of 60 wt %, 65 wt %, 70 wt %, 75 wt % and 80 wt %, or a range therebetween.

[0183] In some embodiments, the fineness of the third positive electrode slurry is ≤45 μm. As an example, the fineness of the third positive electrode slurry can be any one of 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm and 45 μm, or a range between any two thereof.

[0184] Since the battery provided by the embodiment of the present invention adopts all the technical solutions of the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.

[0185] The present invention is further described in detail below by way of examples. The raw materials used in the examples can all be obtained through commercial sources.

[0186] Example 1

[0187] The method for preparing the negative electrode material comprises the following steps:

[0188] (1) The carbon source phenolic resin and asphalt coke (the mass ratio of phenolic resin and asphalt coke is 75:25) are mixed with the auxiliary agent methanol, and sent into a heating furnace and the pore-forming agents carbon dioxide and water (the volume ratio of carbon dioxide and water is 85:15) are introduced. The amount ratio of carbon source, auxiliary agent and pore-forming agent is 100g:3g:1500L. Carbonization is carried out at 1100℃ for 4h. After carbonization, the temperature is lowered to 700℃. Pyrolysis is carried out at 700℃ under an inert atmosphere of nitrogen for 4h. After pyrolysis, the obtained product is washed and crushed to obtain a carbon material matrix precursor with a pore volume of 0.85mL / g and a pore diameter of 0.5nm~3nm, and the pore volume accounts for 91% of the total pore volume;

[0189] (2) mixing a carbon material matrix precursor and a lithium source lithium peroxide, wherein the mass ratio of the carbon material matrix precursor to the lithium source is 100:5.5, calcining the mixture at 700°C for 2 hours under an inert atmosphere of nitrogen, and naturally cooling the obtained product to room temperature after calcination, and then crushing the mixture to obtain a lithium-supplemented carbon material matrix precursor;

[0190] (3) In an inert atmosphere of nitrogen at 450° C., silicon source monosilane was introduced into the lithium-compensated carbon material matrix precursor at a flow rate of 180 mL / h to obtain a lithium-compensated silicon-carbon material having a silicon source deposition amount of 52 wt %;

[0191] (4) The lithium-supplemented silicon-carbon material is used as the core, and is sent to a fluidized bed or a rotary kiln. The temperature is raised to a calcination temperature of 480°C at a rate of 5°C / min, and acetylene, a carbon source, is introduced at a flow rate of 150 mL / h for 18 minutes. The material is kept at the calcination temperature for 2 hours, and a carbon coating layer with a thickness of 24 nm is formed on the surface of the core to obtain a negative electrode material. Based on the mass of the negative electrode material, the carbon content in the negative electrode material is 47.6%, the lithium content is 1.2%, the silicon content is 51%, and the oxygen content is 0.2%.

[0192] In the XRD diffraction pattern of the negative electrode material prepared in Example 1, the peak intensity differential absolute index F1 at the position of 25°~30° is F1=|In(Ii / 2θi)|=4.3; wherein, 2θi=Ix-Iy, Ix and Iy are values ​​taken within 25°~30°, the 2θi value is in the range of 0.02~5, and Ii is the difference between the diffraction peak intensities corresponding to Ix and Iy.

[0193] In the XRD diffraction pattern of the negative electrode material prepared in Example 1, the peak intensity differential absolute index F2 at the position of 45°~55° is F2=|In(Ie / 2θe)|=3.7; wherein, 2θe=Iz-Ir, Iz and Ir are values ​​taken within 45°~55°, the 2θe value is in the range of 0.02~5, and Ie is the difference between the corresponding diffraction peak intensities of Iz and Ir.

[0194] Example 2

[0195] The method for preparing the negative electrode material comprises the following steps:

[0196] (1) The carbon source phenolic resin and asphalt coke (the mass ratio of phenolic resin to asphalt coke is 75:25) are mixed with the auxiliary agent methanol, and sent into a heating furnace and the pore-forming agent carbon dioxide and water are introduced. The amount ratio of carbon source, auxiliary agent and pore-forming agent is 100g:3g:1800L. Carbonization is carried out at 1100℃ for 4h. After the carbonization is completed, the temperature is lowered to 800℃. Pyrolysis is carried out at 800℃ under an inert atmosphere of nitrogen for 4h. After the pyrolysis is completed, the obtained product is washed and crushed to obtain a carbon material matrix precursor with a pore volume of 0.85mL / g and a pore diameter of 0.5nm~3nm, and the pore volume is 90% of the total pore volume;

[0197] (2) mixing a carbon material matrix precursor and a lithium source lithium peroxide, wherein the mass ratio of the carbon material matrix precursor to the lithium source is 100:6.5, calcining the mixture at 700°C for 2 hours under an inert atmosphere of nitrogen, and naturally cooling the obtained product to room temperature after calcination, and then crushing the mixture to obtain a lithium-supplemented carbon material matrix precursor;

[0198] (3) In an inert atmosphere of nitrogen at 450° C., silicon source monosilane was introduced into the lithium-compensated carbon material matrix precursor at a flow rate of 180 mL / h to obtain a lithium-compensated silicon-carbon material having a silicon source deposition amount of 52 wt %;

[0199] (4) The lithium-supplemented silicon-carbon material is used as the core, and is sent to a fluidized bed or a rotary kiln. The temperature is raised to a calcination temperature of 480°C at a rate of 5°C / min, and the carbon source butene is introduced at a flow rate of 100 mL / h for 15 minutes. The material is kept at the calcination temperature for 3 hours, and a carbon coating layer with a thickness of 24 nm is formed on the surface of the core to obtain a negative electrode material. Based on the mass of the negative electrode material, the carbon content in the negative electrode material is 48.1%, the lithium content is 2.4%, the silicon content is 49.3%, and the oxygen content is 0.2%.

[0200] Example 3

[0201] The method for preparing the negative electrode material comprises the following steps:

[0202] (1) The carbon source phenolic resin and asphalt coke (the mass ratio of phenolic resin to asphalt coke is 75:25) are mixed with the auxiliary agent methanol, and sent into a heating furnace and the pore-forming agent carbon dioxide and water are introduced. The amount ratio of carbon source, auxiliary agent and pore-forming agent is 100g:3g:2000L. Carbonization is carried out at 1100℃ for 4h. After the carbonization, the temperature is lowered to 800℃. Pyrolysis is carried out at 650℃ for 4h under an inert atmosphere of nitrogen. After the pyrolysis, the obtained product is washed and crushed to obtain a carbon material matrix precursor with a pore volume of 0.85mL / g and a pore diameter of 0.5nm~3nm, and the pore volume is 93% of the total pore volume;

[0203] (2) mixing a carbon material matrix precursor and a lithium source lithium peroxide, wherein the mass ratio of the carbon material matrix precursor to the lithium source is 100:7.8, calcining the mixture at 700°C for 2 hours under an inert atmosphere of nitrogen, and naturally cooling the obtained product to room temperature after calcination, and then crushing the mixture to obtain a lithium-supplemented carbon material matrix precursor;

[0204] (3) In an inert atmosphere of nitrogen at 450° C., silicon source monosilane at a flow rate of 230 mL / h was introduced into the lithium-compensated carbon material matrix precursor to obtain a lithium-compensated silicon-carbon material having a silicon source deposition amount of 52 wt %;

[0205] (4) The lithium-supplemented silicon-carbon material is used as the core, and is sent to a fluidized bed or a rotary kiln. The temperature is raised to a calcination temperature of 480°C at a rate of 5°C / min, and the carbon source butene is introduced at a flow rate of 150 mL / h for 15 minutes. The material is kept at the calcination temperature for 3 hours, and a carbon coating layer with a thickness of 24 nm is formed on the surface of the core to obtain a negative electrode material. Based on the mass of the negative electrode material, the carbon content in the negative electrode material is 48.3%, the lithium content is 2.5%, the silicon content is 48.8%, and the oxygen content is 0.4%.

[0206] Example 4

[0207] The method for preparing the negative electrode material comprises the following steps:

[0208] (1) The carbon source phenolic resin and asphalt coke (the mass ratio of phenolic resin to asphalt coke is 75:25) are mixed with the auxiliary agent ethanol, and sent into a heating furnace and the pore-forming agent carbon monoxide and water are introduced. The amount ratio of carbon source, auxiliary agent and pore-forming agent is 100g:5g:1800L. Carbonization is carried out at 1100℃ for 4h. After the carbonization is completed, the temperature is lowered to 800℃. Pyrolysis is carried out at 800℃ under an inert atmosphere of nitrogen for 4h. After the pyrolysis is completed, the obtained product is washed and crushed to obtain a carbon material matrix precursor with a pore volume of 0.88mL / g and a pore diameter of 0.5nm~3nm, and the pore volume is 92% of the total pore volume;

[0209] (2) mixing a carbon material matrix precursor and lithium hydroxide as a lithium source, wherein the mass ratio of the carbon material matrix precursor to the lithium source is 100:4, calcining the mixture at 700°C for 2 hours under an inert atmosphere of nitrogen, and naturally cooling the obtained product to room temperature after calcination, and then crushing the mixture to obtain a lithium-supplemented carbon material matrix precursor;

[0210] (3) In an inert atmosphere of nitrogen at 450° C., silicon source monosilane was introduced into the lithium-compensated carbon material matrix precursor at a flow rate of 280 mL / h to obtain a lithium-compensated silicon-carbon material having a silicon source deposition amount of 52 wt%;

[0211] (4) The lithium-supplemented silicon-carbon material is used as the core, and is sent to a fluidized bed or a rotary kiln. The temperature is raised to a calcination temperature of 480°C at a rate of 5°C / min, and the carbon source butene is introduced at a flow rate of 240 mL / h for 10 minutes. The material is kept at the calcination temperature for 3 hours, and a carbon coating layer with a thickness of 24 nm is formed on the surface of the core to obtain a negative electrode material. Based on the mass of the negative electrode material, the carbon content in the negative electrode material is 48.5%, the lithium content is 1.8%, the silicon content is 49%, and the oxygen content is 0.5%.

[0212] Example 5

[0213] The method for preparing the negative electrode material comprises the following steps:

[0214] (1) The carbon source phenolic resin and asphalt coke (the mass ratio of phenolic resin to asphalt coke is 75:25) are mixed with the auxiliary agent ethanol, and sent into a heating furnace and the pore-forming agent carbon monoxide and water are introduced. The amount ratio of the carbon source, the auxiliary agent and the pore-forming agent is 100g:5g:2000L. The mixture is carbonized at 1100°C for 4 hours. After the carbonization, the temperature is lowered to 800°C. The mixture is pyrolyzed at 600°C in an inert atmosphere of nitrogen for 4 hours. After the pyrolysis, the obtained product is washed and crushed to obtain a carbon material matrix precursor with a pore volume of 0.88 mL / g and a pore diameter of 0.5 nm to 3 nm, and the pore volume accounts for 96% of the total pore volume;

[0215] (2) mixing a carbon material matrix precursor and lithium hydroxide as a lithium source, wherein the mass ratio of the carbon material matrix precursor to the lithium source is 100:7, calcining the mixture at 700°C for 2 hours under an inert atmosphere of nitrogen, and naturally cooling the obtained product to room temperature after calcination, and then crushing the mixture to obtain a lithium-supplemented carbon material matrix precursor;

[0216] (3) In an inert atmosphere of nitrogen at 450° C., silicon source monosilane was introduced into the lithium-compensated carbon material matrix precursor at a flow rate of 280 mL / h to obtain a lithium-compensated silicon-carbon material having a silicon source deposition amount of 52 wt%;

[0217] (4) The lithium-supplemented silicon-carbon material is used as the core, and is sent to a fluidized bed or a rotary kiln. The temperature is raised to a calcination temperature of 480°C at a rate of 5°C / min, and the carbon source butene is introduced at a flow rate of 400 mL / h for 6 minutes. The material is kept at the calcination temperature for 3 hours, and a carbon coating layer with a thickness of 24 nm is formed on the surface of the core to obtain a negative electrode material. Based on the mass of the negative electrode material, the carbon content in the negative electrode material is 48.3%, the lithium content is 2.2%, the silicon content is 49%, and the oxygen content is 0.5%.

[0218] Example 6

[0219] The method for preparing the negative electrode material comprises the following steps:

[0220] (1) The carbon source phenolic resin and asphalt coke (the mass ratio of phenolic resin to asphalt coke is 75:25) are mixed with the auxiliary agent ethanol, and sent into a heating furnace and the pore-forming agent carbon monoxide and water are introduced. The amount ratio of carbon source, auxiliary agent and pore-forming agent is 100g:5g:2500L. Carbonization is carried out at 1100℃ for 4h. After the carbonization is completed, the temperature is lowered to 800℃ and pyrolysis is carried out at 580℃ for 3h in an inert atmosphere of nitrogen. After the pyrolysis is completed, the obtained product is washed and crushed to obtain a carbon material matrix precursor with a pore volume of 0.93mL / g and a pore diameter of 0.5nm~3nm, and the pore volume is 93% of the total pore volume;

[0221] (2) mixing a carbon material matrix precursor and a lithium source lithium chloride, wherein the mass ratio of the carbon material matrix precursor to the lithium source is 100:9, calcining the mixture at 700°C for 2 hours under an inert atmosphere of nitrogen, and naturally cooling the obtained product to room temperature after calcination, and then crushing the mixture to obtain a lithium-supplemented carbon material matrix precursor;

[0222] (3) In an inert atmosphere of nitrogen at 450° C., silicon source monosilane at a flow rate of 300 mL / h was introduced into the lithium-compensated carbon material matrix precursor to obtain a lithium-compensated silicon-carbon material having a silicon source deposition amount of 52 wt %;

[0223] (4) The lithium-supplemented silicon-carbon material is used as the inner core and is sent to a fluidized bed or a rotary kiln. The temperature is raised to a calcination temperature of 480°C at a rate of 5°C / min, and acetylene, a carbon source, is introduced at a flow rate of 400 mL / h for 18 minutes. The material is kept at the calcination temperature for 3 hours, and a carbon coating layer with a thickness of 24 nm is formed on the surface of the inner core to obtain a negative electrode material. Based on the mass of the negative electrode material, the carbon content in the negative electrode material is 47.1%, the lithium content is 1.5%, the silicon content is 51.2%, and the oxygen content is 0.2%.

[0224] Comparative Example 1

[0225] The difference between this comparative example and Example 1 is that:

[0226] In step (1), no auxiliary agent was added, and the ratio of carbon source to pore-forming agent was 100 g:1500 L.

[0227] The rest are the same as in Example 1.

[0228] Comparative Example 2

[0229] The difference between this comparative example and Example 1 is that:

[0230] In step (2), no lithium source is added.

[0231] The rest are the same as in Example 1.

[0232] Comparative Example 3

[0233] The difference between this comparative example and Example 1 is that:

[0234] In the XRD diffraction pattern of the negative electrode material prepared in this comparative example, the peak intensity differential absolute index F1 at the position of 25°~30° is F1=|In(Ii / 2θi)|=8.2; wherein, 2θi=Ix-Iy, Ix and Iy are values ​​taken within 25°~30°, the 2θi value is in the range of 0.02~5, and Ii is the difference between the diffraction peak intensities corresponding to Ix and Iy.

[0235] In the XRD diffraction pattern of the negative electrode material prepared in Example 1, the peak intensity differential absolute index F2 at the position of 45°~55° is F2=|In(Ie / 2θe)|=6.4; wherein, 2θe=Iz-Ir, Iz and Ir are values ​​taken within 45°~55°, the 2θe value is in the range of 0.02~5, and Ie is the difference between the corresponding diffraction peak intensities of Iz and Ir.

[0236] Performance Testing

[0237] 1. Preparation of secondary batteries

[0238] (1) The negative electrode active material (the negative electrode material prepared in the above embodiment and comparative example) and the conductive agent conductive carbon black were mixed and dispersed for 45 minutes, and then the binder lithium polyacrylate and the solvent water were added and mixed and dispersed for 90 minutes to obtain a first negative electrode slurry; the first negative electrode material, the conductive agent single-walled carbon nanotubes, part of the binder lithium polyacrylate and the solvent water were mixed and dispersed for 90 minutes to obtain a second negative electrode slurry with a solid content of 48wt%; the second negative electrode slurry, the binder lithium polyacrylate and the solvent water were mixed to obtain a third negative electrode slurry with a solid content of 42wt% and a fineness of ≤45μm, and the mass ratio of the negative electrode active material, the conductive agent and the binder in the third negative electrode slurry was 95.3:1.5:3.2; the third negative electrode slurry was coated on a foil, and the surface density was controlled to be 0.07g / cm 2 , drying to remove solvent water, rolling, drying, and die-cutting to obtain the negative electrode sheet.

[0239] (2) The positive electrode active material and the conductive agent conductive carbon black are mixed and dispersed for 30 minutes, and then the binder lithium polyacrylate and the solvent N-methylpyrrolidone (NMP) are added and mixed and dispersed to obtain a first positive electrode slurry; the first positive electrode material, the conductive agent (single-walled carbon nanotubes and multi-walled carbon nanotubes, the mass ratio is 75:25) the binder lithium polyacrylate, the electrolyte lithium lanthanum zirconate and the solvent NMP are mixed and dispersed for 90 minutes to obtain a second positive electrode slurry with a solid content of 81wt%; the second positive electrode slurry, the binder lithium polyacrylate and the solvent NMP are mixed to obtain a third positive electrode slurry with a solid content of 72wt% and a fineness of ≤45μm, and the mass ratio of the positive electrode active material, the conductive agent, the binder and the electrolyte in the third positive electrode slurry is 97.7:0.9:1.2:0.2; the third positive electrode slurry is coated on the foil, and the surface density is controlled at 0.022g / cm 2 , drying to remove the solvent NMP, rolling, drying, and die-cutting to obtain the positive electrode sheet.

[0240] (3) Stack the positive electrode sheet, separator, and negative electrode sheet, weld the aluminum tab to the positive electrode sheet, weld the copper tab to the negative electrode sheet, install the shell, inject liquid, form the battery, and divide the capacity to make a secondary battery.

[0241] 2. Preparation of button batteries

[0242] The above-mentioned negative electrode material, conductive carbon black, polyacrylonitrile binder and single-walled carbon nanotubes were homogenized in a mass ratio of 79.8:10:10:0.08 to prepare a negative electrode sheet, which was assembled into a button battery using a lithium sheet as the positive electrode.

[0243] 3. Conduct electrochemical performance tests on button batteries and secondary batteries

[0244] (1) The button-type batteries made of the negative electrode materials in the above examples and comparative examples were subjected to the initial performance test. The specific test method is as follows:

[0245] Initial efficiency test: Tested on a Blue Electric test system, the battery was charged at a constant current of 0.1C to 0.005V, resulting in a charge capacity of 1. After a 2-minute hold, the battery was then charged at a constant current of 0.02C to 0.005V, resulting in a charge capacity of 2. After a 2-minute hold, the battery was discharged at a constant current of 0.1C to 1.5V, resulting in a discharge capacity of 1. Initial efficiency = discharge capacity 1 / (charge capacity 1 + charge capacity 2). The test results are shown in Table 1.

[0246] Table 1

[0247] Group First effect Example 1 96.0% Example 2 99.3% Example 3 104.8% Example 4 97.2% Example 5 115.0% Example 6 105.7% Comparative Example 1 87.2% Comparative Example 2 89.3% Comparative Example 3 88.8%

[0248] (2) Test the first efficiency and 2C discharge capacity of the secondary battery. Specific test methods:

[0249] First efficiency test: Capacity reduction stage: The secondary battery is first charged with a constant current of 0.5C current (1C current = 3.5A) to 4.25V, then charged with a constant voltage of 4.25V until the current drops to 0.025C, and the capacity is recorded as C1. After standing for 5 minutes, the battery is discharged with a current of 0.5C to 2.8V, and the capacity is recorded as C2. Therefore, the first efficiency = C2 / C1.

[0250] 2C discharge capacity test: A 2C discharge test was conducted on an electrochemical workstation: constant current charge at 0.5C (1C current = 3.5A) to 4.25V, hold for 5 minutes, then constant voltage charge at 4.25V until the current dropped to 0.025C, hold for 5 minutes, discharge at 0.5C to 2.8V, record the capacity as C3, hold for 5 minutes, constant current charge at 0.5C (1C current = 3.5A) to 4.25V, then constant voltage charge at 4.25V until the current dropped to 0.025C, hold for 5 minutes, discharge at 2.0C to 2.8V, record the capacity as C4. Therefore, 2C discharge capacity = C4 / C3×100%.

[0251] The test results are shown in Table 2.

[0252] Table 2

[0253] Group First effect / % 2C discharge capability Example 1 92.4% 96.4% Example 2 93.5% 96.8% Example 3 94.3% 97.3% Example 4 92.2% 95.8% Example 5 93.4% 96.2% Example 6 93.7% 97.9% Comparative Example 1 92.0% 87.0% Comparative Example 2 89.0% 85.0% Comparative Example 3 81.3% 92.1%

[0254] Combining Table 1 and Table 2, it can be seen that the 1.5V first effect and 2C discharge capacity of Comparative Examples 1 to 3 are lower than the 1.5V first effect and 2C discharge capacity of the embodiment, which shows that in Comparative Example 1: the addition of additives is beneficial to the activation of porous carbon and reduces the proportion of invalid pores (pores < 0.5nm). In Comparative Example 2: the supplementation of lithium source leads to an increase in the proportion of reversible lithium in the negative electrode material, reduces dependence on lithium in the electrolyte, and improves the lithium ion conductivity of the material. In Comparative Example 3: through the XRD diffraction pattern, the peak intensity differential absolute index of the negative electrode material is controlled, the silicon crystal of the negative electrode material is smaller, the influence of the lithium insertion expansion of the negative electrode material is reduced, and the material stability is higher. In short, the above adjustments can improve the material's electron conductivity efficiency, reduce current polarization, accelerate the diffusion of lithium ions and the transfer of charge, thereby improving the 1.5V first effect and 2C discharge capacity.

[0255] Parts of the present invention that are not described in detail are well known to those skilled in the art.

[0256] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A negative electrode material, characterized in that The negative electrode material comprises a core and a carbon coating layer coated on at least a portion of the surface of the core; The core comprises a carbon material matrix and a modified material, wherein the modified material comprises lithium and / or a lithium-containing compound, and silicon and / or a silicon-containing compound; The carbon material matrix has a porous structure, and the modifying material is attached to the porous structure.

2. The negative electrode material according to claim 1, characterized in that The modified material includes lithium, silicon, lithium silicon alloy and lithium silicate, and the lithium, silicon, lithium silicon alloy and lithium silicate are attached to the porous structure; Preferably, the lithium-silicon alloy comprises Li m Si n , where 0 < m ≤ 22, 0 < n ≤ 7, and 0 < m / n ≤ 4.4; Preferably, the lithium silicate includes Li x Si y O z , where 0 ≤ x ≤ 22, 0 < y ≤ 7, 0 ≤ z ≤ 4, and 0 < x / y ≤ 4.

4.

3. The negative electrode material according to claim 1, characterized in that: In the XRD diffraction pattern of the negative electrode material, the peak intensity differential absolute index F1 at the position of 25° to 30° is F1=|In(Ii / 2θi)|, and 1.8≤F1≤6.5; wherein 2θi=Ix-Iy, Ix and Iy are values ​​taken within 25° to 30°, the 2θi value is in the range of 0.02 to 5, and Ii is the difference between the diffraction peak intensities corresponding to Ix and Iy; And / or, in the XRD diffraction pattern of the negative electrode material, the peak intensity differential absolute index F2 at the position of 45° to 55° is F2 = |In(Ie / 2θe)|, and 1.2≤F2≤5.3; wherein, 2θe = Iz-Ir, Iz and Ir are values ​​taken within 45° to 55°, the 2θe value is in the range of 0.02 to 5, and Ie is the difference between the diffraction peak intensities corresponding to Iz and Ir.

4. The negative electrode material according to any one of claims 1 to 3, characterized in that The negative electrode material satisfies at least one of the following characteristics (1) to (8): (1) Based on the mass of the negative electrode material, the mass content of the carbon material matrix is ​​35% to 65%; (2) The modified material includes lithium, silicon, lithium-silicon alloy and lithium silicate, and the mass content of the lithium element is 0.2% to 60% based on the mass of the negative electrode material; (3) The modified material includes lithium, silicon, lithium-silicon alloy and lithium silicate, and the mass content of the silicon element is 0.2% to 60% based on the mass of the negative electrode material; Preferably, the mass content of the lithium element is less than or equal to the mass content of the silicon element; (4) The modified material includes lithium, silicon, lithium-silicon alloy and lithium silicate, and the mass content of the lithium-silicon alloy is ≤10% based on the mass of the negative electrode material; (5) The modified material includes lithium, silicon, lithium-silicon alloy and lithium silicate, and the mass content of the lithium silicate is ≤10% based on the mass of the negative electrode material; (6) The thickness of the carbon coating layer is 0.8 nm to 80 nm; (7) The particle size D of the negative electrode material v 50 is 2μm~35μm; (8) The tap density of the negative electrode material is 0.6 to 1.4 m 3 / g.

5. A method for preparing a negative electrode material, characterized in that: The following steps are involved: S100, mixing a carbon material matrix precursor and a lithium source, and performing a first calcination to obtain a lithium-supplemented carbon material matrix precursor; S200, introducing a silicon source into a lithium-supplemented carbon material matrix precursor to perform cracking and deposition to obtain a lithium-supplemented silicon-carbon material; S300: Using the lithium-supplemented silicon-carbon material as a core, introducing a first carbon source into the lithium-supplemented silicon-carbon material, and performing a second calcination to form a carbon coating layer on at least part of the surface of the core, wherein the core includes a carbon material matrix with a porous structure and a modifying material attached to the porous structure, to obtain a negative electrode material.

6. The method for preparing the negative electrode material according to claim 5, characterized in that: In step S100, the mass ratio of the carbon material matrix precursor to the lithium source is 100:(0.2-12); Preferably, in step S100, the pore volume of the carbon material matrix precursor is 0.65 mL / g to 1.2 mL / g; Preferably, based on the total pore volume of the carbon material matrix precursor, the volume of pores with a diameter of 0.5 nm to 3 nm in the carbon material matrix precursor is ≥ 90%; Preferably, the method for preparing the carbon material matrix precursor comprises the following steps: After mixing the second carbon source and the auxiliary agent, a pore-forming agent is introduced, followed by carbonization, cooling, and pyrolysis to obtain a carbon material matrix precursor; Preferably, the lithium source includes at least one of metallic lithium, phenyllithium, butyllithium, lithium silicon alloy powder, lithium hydroxide, lithium peroxide, lithium oxide, lithium nitride, lithium sulfide and lithium fluoride; And / or, in step S100, the temperature of the first calcination is 300° C. to 1300° C., the time of the first calcination is 30 minutes to 5 hours, and the atmosphere of the first calcination is an inert gas.

7. The method for preparing the negative electrode material according to claim 6, wherein: The method for preparing the carbon material matrix precursor satisfies at least one of the following conditions (1) to (4): (1) The dosage ratio of the second carbon source, the auxiliary agent and the pore-forming agent is 100 g: (0.1-5) g: (200-2500) L; Preferably, the second carbon source comprises at least one of carbon black, coconut shell, bamboo, oak, phenolic resin, epoxy resin, furfural resin, urea-formaldehyde resin, needle coke, pitch coke, petroleum coke and mesocarbon microbeads; Preferably, the auxiliary agent includes at least one of methanol, ethanol, propanol and isopropanol; Preferably, the pore-forming agent comprises at least one of oxygen, hydrogen, carbon monoxide, carbon dioxide, water and ammonia; (2) The carbonization temperature is 900° C. to 1400° C., and the carbonization time is 3 h to 14 h; (3) The final temperature of the cooling is 400° C. to 900° C.; (4) The pyrolysis temperature is 400°C to 900°C, the pyrolysis time is 2h to 8h, and the pyrolysis atmosphere is an inert gas.

8. The method for preparing the negative electrode material according to claim 5, wherein: In step S200, the flow rate of the silicon source is 100 mL / h to 400 mL / h; And / or, in step S200, the temperature of the pyrolysis deposition is 400-760° C., the time of the pyrolysis deposition is 20 min-6 h, and the atmosphere of the pyrolysis deposition is an inert gas; And / or, in step S200, the deposition amount of the silicon source is 15 wt% to 80 wt% of the lithium-supplemented silicon-carbon material; And / or, in step S200, the silicon source includes at least one of monosilane, disilane, trisilane, dimethylsilane, hexamethyldisilane, dichlorodihydrogen silicon, trichlorosilane, silicon tetrachloride or silicon tetrafluoride.

9. The method for preparing a negative electrode material according to any one of claims 5 to 8, characterized in that: In step S300, the flow rate of the first carbon source is 20 mL / h to 300 mL / h; And / or, in step S300, the first carbon source includes at least one of butene, ethylene, butyne, acetylene and propyne; And / or, in step S300, the heating rate of the second calcination is 1°C / min to 8°C / min, the temperature of the second calcination is 400 to 700°C, and the time of the second calcination is 1 hour to 6 hours.

10. A battery comprising a negative electrode sheet, characterized in that: The negative electrode sheet comprises the negative electrode material according to any one of claims 1 to 4, or comprises a negative electrode material prepared by the preparation method of the negative electrode material according to any one of claims 5 to 9.